Technology audit process of nitro mixture preparing process for benzene and toluene nitration using non concentrated nitric acid - Красильникова, Анна Александровна; Кондратов, Сергей Алексеевич (Technology audit and production reserves, 2015)
It is developed a computer model of the material and thermal balance of preparation stage of nitration mixture and local concentration of the waste sulfuric acid in the nitration of benzene and toluene with concentrated nitric acid containing 26-28 % of the main substance. The basis of the model is preparation of nitration mixture formally containing α kg of waste acid per 1 kg of base nitration mixture which composition is determined by the type nitrate connection. Nitration mixture is prepared from concentrated nitric acid and working sulfuric acid, obtained by a local concentration of waste acid. The heat input on the concentration of spent acid to a standard 92 % acid in the plant-wide units is used as a basis of comparison. The simulation shows that the use of concentrated nitric acid in combination with a local concentration of the waste acid from the viewpoint of energy is more advantageous than the traditional use of deficient high-concentration nitric acid. This is due to the fact that the process of local concentration of the waste acid to the desired working concentration is more beneficial than centralized concentration to 92-96 % acid. With increasing value α, a positive effect on the local concentration increases, and with increasing the residual pressure in the distillation of water (from 13,3 to 80 kPa – decreases. The latter is associated with increase in the boiling temperature and enthalpy of the final state.